2013
DOI: 10.1111/jam.12372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acclimation medium on cell viability, membrane integrity and ability to consume malic acid in synthetic wine by oenologicalLactobacillus plantarumstrains

Abstract: Aims: The aim of this work was to evaluate the effect of acclimation on the viability, membrane integrity and the ability to consume malic acid of three oenological strains of Lactobacillus plantarum. Methods and Results: Cultures in the stationary phase were inoculated in an acclimation medium (Accl.) containing 0, 6 or 10% v/v ethanol and incubated 48 h at 28°C. After incubation, cells were harvested by centrifugation and inoculated in a synthetic wine, containing 14% v/v ethanol and pH 3Á5 at 28°C. Viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…§Initial inoculum 1 9 10 7 CFU ml À1 . ¶Results previously reported in Bravo-Ferrada et al 2014. The relationship between resistance to ethanol and increase of the short-length fatty acid reflects the complexity of the mechanisms involved. van Bokhorst-van de Veen et al (2011) reported that ethanol stress affects the expression of Lact.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…§Initial inoculum 1 9 10 7 CFU ml À1 . ¶Results previously reported in Bravo-Ferrada et al 2014. The relationship between resistance to ethanol and increase of the short-length fatty acid reflects the complexity of the mechanisms involved. van Bokhorst-van de Veen et al (2011) reported that ethanol stress affects the expression of Lact.…”
Section: Resultsmentioning
confidence: 93%
“…To investigate the influence of fatty acid composition on the technological properties of strains, the alterations occurred upon acclimation were correlated with the viability and MAC previously reported (Bravo-Ferrada et al 2014). The log CFU ml À1 reported in Table 1 corresponds to the viability of strains after 15 days of incubation at 28°C (initial inoculum:~10 7 CFU ml À1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…plantarum to survive to specific stress factors encountered in wine (e.g., acid pH, cold), as well as other stress factors in various foods (e.g., bile, osmotic, heat, high pressure) was widely explored (van de Guchte et al, 2002; De Angelis and Gobbetti, 2011). Moreover, in recent years some Authors (Bravo-Ferrada et al, 2013, 2014, 2015, 2016) reported the positive effect of acclimation to ethanol concentrations lower than that of wine on the viability and malic acid consumption of oenological Lb. plantarum strains.…”
Section: Introductionmentioning
confidence: 99%